2001
DOI: 10.1046/j.1365-2109.2001.00579.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of preservation techniques and freezing storage time on biochemical composition and spectrum of fatty acids ofIsochrysis galbanaclone T-ISO

Abstract: Isochrysis galbana clone T‐ISO was cultured in 5‐L vessels with continuous light at 100 µmol photons m−2 s−1 at temperature room (22 °C) and harvested at early exponential phase. Dry weight (dw), ash content, biochemical composition and fatty acid profile were determined in fresh biomass and after storage for 7 days and 3 months at −76 °C for both freeze‐dried and frozen biomasses. Both freezing and freeze‐drying caused significant losses in dry weight (range 13.67–19.74%) when compared with fresh microalgae (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 24 publications
0
13
3
Order By: Relevance
“…This is in contrast to what Esquivel et al 5 observed, but similar to the result of Babarro et al 9 A possible explanation for these contradicting results is storage of the fresh microalgal paste prior to processing. As shown in this research, even very short term storage of fresh biomass can lead to pronounced lipolysis and lower amounts of measured lipid content.…”
Section: Influence Of Storage Time and Conditions After Freeze-contrasting
confidence: 78%
“…This is in contrast to what Esquivel et al 5 observed, but similar to the result of Babarro et al 9 A possible explanation for these contradicting results is storage of the fresh microalgal paste prior to processing. As shown in this research, even very short term storage of fresh biomass can lead to pronounced lipolysis and lower amounts of measured lipid content.…”
Section: Influence Of Storage Time and Conditions After Freeze-contrasting
confidence: 78%
“…Some enzymes are also inactivated during the drying process, depending on the time and temperature used. This was, however, not observed by Babarro et al (2001) after freeze-drying of Isochrysis galbana, by Ryckebosch et al (2011) after freezedrying and spray drying of P. tricornutum and by Balasubramanian et al (2013) after hot air drying, sun drying, and freeze-drying of Nannochloropsis. Autoxidation is also dependent on water activity, since the oxidation rate decreases when drying until a water activity of about 0.2, but increases again when water activity is lower than 0.2 ( Figure 2) (Belitz et al, 2009;Kerr, 2013).…”
Section: Stability Of Lipids During Dry Storage Of Microalgal Biomassmentioning
confidence: 71%
“…Babarro et al . () observed that the lipid composition (including DHA) of another microalgal species remains unchanged in frozen cells after 3 months of storage at −76 °C. Moreover, Guevara et al .…”
Section: Resultsmentioning
confidence: 97%
“…Prior to DSC determinations, both fresh and frozen-stored microalgal cells were dehydrated by freeze-drying in a Heto Holten A/S, cooling trap model CT 110 freeze-dryer (Heto Lab Equipment, Allerød, Denmark ), to improve the intensity of the signal. It was reported that this method maintained microalgal lipid composition (Babarro et al, 2001;Ryckebosch et al, 2011). The chloroform extracts were dried with a nitrogen flux and were immediately analysed by DSC.…”
Section: Stability Of Frozen Microalgal Cellsmentioning
confidence: 99%
See 1 more Smart Citation